Дифузiя на деформованiй поверхнi фермi - Kolomietz, V. M.; Lukyanov, S. V. (Publishing house "Academperiodika", 2018)
The diffusion approximation to the relaxation on the distorted Fermi surface in a Fermi liquid is considered. The dependence of the relaxation time on the multipolarity of a Fermi surface deformation is established. The time evolution of the non-equilibrium particle-hole excitations is studied.